Contrast-enhanced ultrasound with sub-micron sized contrast agents detects insulitis in mouse models of type1 diabetes - David G. Ramirez (Nature Portfolio, 2020)
Infiltration of immune cells to the pancreatic islets precedes clinical symptoms of type 1 diabetes, and lack of methods to detect this insulitis impedes early interventions. Here the authors report a contrast enhanced ultrasound method that can detect early insulitis in mouse models of type 1 diabetes, based on increased microvascular permeability.